2020
DOI: 10.1021/acssynbio.0c00002
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Generation, Tracking, and Functional Screening of Substitution Mutants Using a CRISPR/Retron System

Abstract: We developed a clustered regularly interspaced short palindromic repeats (CRISPR)/retron system for multiplexed generation of substitution mutations by co-utilization of a retron system that continuously expresses donor DNA and a CRISPR/Cas9 cassette that induces cleavage at target genomic loci. Our system efficiently introduces substitution mutation in the Escherichia coli genome in a high-throughput manner. These substitution mutations can be tracked by analysis of retron plasmid sequences without laborious … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Moreover, retron recombineering technologies have also been used in combination with CRISPR–Cas systems for multiplex gene editing in bacteria (Lim et al . 2020 ) and eukaryotes (Sharon et al . 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, retron recombineering technologies have also been used in combination with CRISPR–Cas systems for multiplex gene editing in bacteria (Lim et al . 2020 ) and eukaryotes (Sharon et al . 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that retrons coupled with CRISPR-Cas9 could enhance precise genome editing via HDR in bacterium and yeast through fusing guide RNA (gRNA) to the 3′ end of retron ncRNA, producing multicopy single-stranded DNA (msDNA) covalently tethered to gRNA (Sharon et al, 2018 ; Lim et al, 2020 ; Schubert et al, 2021 ). In this study, we further engineered retrons by fusing Cas9 with E. coli RT from different clades and joining gRNA at the 5′ end of retron ncRNA, and found that retron editing can achieve precise genome editing efficiently in human cells.…”
mentioning
confidence: 99%
“…RLR overcomes the requirement for targeting a suitable PAM altogether, whereas CRISPR "guide + donor" methods decrease in performance as the distance to a PAM increases (26)(27)(28). Intriguingly, production of a retron ssDNA donor appears to improve CRISPR "guide + donor" methods in Saccharomyces cerevisiae (26) and E. coli (46), presumably by making the recombination donor more abundant or accessible.…”
Section: Discussionmentioning
confidence: 99%